Liquid- Liquid extraction method for extraction Zn(II) and Cd(II) from aqueous solutions by two synthesized azo organic reagent. - Jawad, Shawket K.; AL-Ghurabi, Fatima A. Wannas (Al-Qadisiyah Journal of Pure Science, 2017)
2-[2-pyridil azo]-4-benzen naphthol [PABN] and 2-[(4-Hydroxy phenyl azo]-4,5-diphenyl imidazol [HPADPI] were Synthesized and used for the extraction of Zn(II) and Cd(II) from aqueous solutions. Effective factors on the extraction method was investigated stoichiometry shows the complex extracted was [M+2(PABN-(Cl-)] and [M+2(HPADPI)]2Cl- when (M2+=Zn2+,Cd2+), Thermodynamic studies appeared complexation reaction for Zn2+,Cd2+ with both organic reagents was endothermic, in addition of another studies.